Efektivitas Penggunaan Teknologi dalam Meningkatkan Strategi Pembelajaran Interaktif di Kelas - Ahsan Nadya; Salman Shiddiq; Gusmaneli Gusmaneli (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
In education in the 4.0 era, teachers should pay attention to the strategies used in the learning process and also the technology coverage that helps to facilitate the application of learning so that the learning goals formulated are well achieved. Interactive learning strategies can support learning processes with the use of technology as a learning medium. In this paper, the author uses the study of literature (Library Research) by collecting data from various sources such as books, scientific journals, dissertations, and online sources related to the effectiveness of the use of technology in enhancing interactive learning strategies. Conclusion The interactive learning strategy is an approach that encourages students to think critically, share opinions, and conduct research on their own questions. The use of media and technology, such as video and animation, can also improve learning effectiveness. Video enables students to understand material better, while animation can arouse students' interest in learning.